(untitled) (Estudios humanísticos. Geografía, historia y arte, 1995)
In this article we have attempted to develop a synthesis of the kinship systems through which this type of society has achieved its adaptation to the environment. The study is based on the basic methodologies in the development of anthropological work. The main tool was on-field work including participative observation and opera interviews, which cannot be detailed due to space limitations. A basic bibliography was also used to frame the work in the scope of Social Anthropology and specifically in kinship studies. The approach to subject was based on the features of the two basic types of family -trunk and nuclear family- and the inheritance systems based on male primogeniture in the former type. We focus on the trunk family due to its clear preeminence in the valley over the nuclear type and to the fact that this type of family is extremely infrequent among kinship systems today. We perform an indepth study of the system of inheritance showing the different types of entailment through history. Lastly we have attempted to state clearly the differences and affinities between these historical types and the current inheritance system.